2000
DOI: 10.1021/tx990135m
|View full text |Cite
|
Sign up to set email alerts
|

Transalkylation of Phosphotriesters Using Cob(I)alamin:  Toward Specific Determination of DNA−Phosphate Adducts

Abstract: The supernucleophilic cobalt compound, cob(I)alamin, has been kinetically characterized with respect to its ability to bring about transalkylation of adducts to DNA phosphates (phosphotriesters). The reactivity of cob(I)alamin toward different phosphotriesters (model compounds and methylated DNA), as well as its specificity toward DNA-phosphate adducts, has been investigated. Through nucleophilic displacement on the alkyl by cob(I)alamin, the alkyl groups (methyl and ethyl) were transferred from phosphotrieste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…[4] Cbl(I) dehalogenates or dealkylates a wide range of organic molecules, including alkanes, alkenes, alkynes, aromatics, and phosphotriesters. [4,11] There is also much interest in using Cbl(I) to trap reactive intermediates such as oxiranes. [12] Kinetic studies have been reported for the dehalogenation of halogenated alkanes, [13] alkenes, [14] and acetic acid [15] and the dealkylation of phosphotriesters.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Cbl(I) dehalogenates or dealkylates a wide range of organic molecules, including alkanes, alkenes, alkynes, aromatics, and phosphotriesters. [4,11] There is also much interest in using Cbl(I) to trap reactive intermediates such as oxiranes. [12] Kinetic studies have been reported for the dehalogenation of halogenated alkanes, [13] alkenes, [14] and acetic acid [15] and the dealkylation of phosphotriesters.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysate of ENU-treated DNA was transalkylated using cob(I)alamin according to an earlier developed method [17]. DNA sample (100 L) was added to a reduced cobalamin solution under argon.…”
Section: Transalkylation By Cob(i)alaminmentioning
confidence: 99%
“…The program used was the following: Samples were injected on the pre-column using the auxiliary system C at [15][16][17][18][19][20] L/min. At the same time the binary system A/B pumps 20% Solvent B at a flow of 2-8 L/min over the analytical column.…”
Section: Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of Cbl as an analytical tool has been demonstrated in earlier studies where Cbl has been utilized for transfer and analysis of adducts to phosphate oxygens in DNA [7] and for investigation of the reactivity of 1,2-epoxides [8]. The main advantage of Cbl compared to other standard nucleophiles, e. g., thiosulfate and nicotinamide [7,8] is that Cbl in its reduced form [Cbl(I)] is by orders of magnitude more reactive.…”
Section: Introductionmentioning
confidence: 99%